2016
DOI: 10.1016/j.ejogrb.2016.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative fetal fibronectin predicts preterm birth in women with bulging fetal membranes

Abstract: Please cite this article as: FIORINI F, ISTED A, HEZELGRAVE NL, SHENNAN AH, Quantitative fetal fibronectin predicts preterm birth in women with bulging fetal membranes, European Journal of Obstetrics and Gynecology and Reproductive Biology (2016), http://dx.doi.org/10. 1016/j.ejogrb.2016.05.046 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To our knowledge, this is the first study looking at the prognostic value of fFN among women requiring emergency cerclage for exposed membranes. Our group has previously demonstrated the prognostic value of fFN among women with risk factors for preterm labour but without exposed membranes 10 and more recently with exposed membranes 11 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To our knowledge, this is the first study looking at the prognostic value of fFN among women requiring emergency cerclage for exposed membranes. Our group has previously demonstrated the prognostic value of fFN among women with risk factors for preterm labour but without exposed membranes 10 and more recently with exposed membranes 11 .…”
Section: Discussionmentioning
confidence: 93%
“…Our group has previously demonstrated the predictive value of quantitative fFN measurement in women presenting with symptoms of preterm labour, with added risk discrimination over and above the traditional qualitative test, as well as in asymptomatic women at high risk of preterm birth 10 . Furthermore, we have shown that even in women with exposed membranes, a group traditionally thought to be at universally high risk of preterm birth, the risk of preterm birth still correlates with qfFN concentration in the cervicovaginal fluid 11 .…”
Section: Introductionmentioning
confidence: 88%
“…Table 1 presents the data from the included studies. Of the 15 studies, 13 described diagnostic performance of 10 ng/ml, 6,10–21 15 used 50 ng/ml, 6,10–23 12 used 200 ng/ml, 6,10–19,21 and 7 used 500 ng/ml 6,10,11,13,14,19,21 . Detailed information regarding study design, sample size, age of participants, and the thresholds used in each study is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for the construction of the 500 ng/ml threshold is because this is the upper limit reported by the 10Q analyzer (similar technology is used in both qualitative and quantitative tests). Previous researchers have suggested a relatively high incidence (75%, 89%, and 100%) of sPTB in women with quantitative fFN ≥500 ng/ml while its diagnostic accuracy is still controversial 7,13,19 . As a novel predefined threshold, 500 ng/ml presents the lowest sensitivity but the best specificity (99%)—namely, the 500 ng/ml threshold is extremely effective in the identification of women who are at low‐risk of sPTB.…”
Section: Discussionmentioning
confidence: 99%